Public Perception, Knowledge, and Participation in Climate Change Adaptation Governance in the Coastal Region of Bangladesh Using the Social Ecological Inventory (SEI) Tool - Bahauddin, Khalid Md.; Rahman, Nasibul; Hasnine, Md Tanvir (TAYLOR & FRANCIS LTD, 2016)
Public participation is commonly advocated for as part of policy responses to climate change. This study examines the prospects for inclusive approaches to climate change adaptation, drawing particularly on studies of long-term climate change adaptation in a coastal region in Bangladesh. It has been suggested that public perception, knowledge, and participation are important goals in the process of formulating response to climate change risks. This study found that local people as well as other stakeholders who participated in the study were more or less familiar with the term climate change. However, the participants' understanding of what the term means and climate change's causes varied widely. The results also showed that a large number of the participants were uncertain about the solution to the climate change problems they are already experiencing, due to lack of accessible information from different governmental and non-governmental sources. It is notable that, despite being a country with a high level of political commitment to dealing with climate change, supported by plans, programs, and interventions, the people of Bangladesh are largely unaware of these efforts. This study explores the Social Ecological Inventory (SEI) tool as a means of managing the governance system for climate change adaptation in order to explore the public's perception of, knowledge about, and participation in developing adaptation plans. In this study, we used the SEI tool to systemically map the values, motives, activities, knowledge, and experiences of different actors over time and in different networks in order to prepare the ground for participation in developing climate change adaptation plans by helping identify and select the most appropriate set of actors to work with; build trust between these different actors; and, finally, reach a consensus among actors on how to enhance a region's sustainability and resilience.
Keywords: ADAPTIVE GOVERNANCE; MANAGEMENT; RESILIENCE; CAPACITY; VULNERABILITY; COMANAGEMENT; Environmental Sciences & Ecology